MENA Quarterly Economic Brief, January 2015 : Plunging Oil Prices - Devarajan, Shanta; Mottaghi, Lili (Washington, DC: World Bank, 2015)
This issue of the MENA Quarterly Economic Brief focuses on the implications of low oil prices for eight developing countries, or the MENA-8 (oil importers: Egypt, Tunisia, Lebanon and Jordan and oil exporters: Iran, Iraq, Yemen and Libya) and the economies of the GCC (Gulf Cooperation Council), who play a major role in providing funds in the form of aid, investment, tourism revenues and remittances to the rest of the countries of the region. We make the following assumptions about the future price of oil: (i) The price will average $65 Brent p/b in 2015; (ii) a higher price $78 Brent p/b will be used for comparison analysis. As with other economic variables, there is uncertainty associated with the future price of oil, which adds to the error involved in projections. The data for 2015 2017 in the figures and tables are projections. These projections are based on statistical information available through early January 2015.